2015
DOI: 10.1002/term.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cells for tissue engineering of cardiac valves

Abstract: Heart valve tissue engineering is a promising alternative to prostheses for the replacement of diseased or damaged heart valves, because tissue-engineered valves have the ability to remodel, regenerate and grow. To engineer heart valves, cells are harvested, seeded onto or into a three-dimensional (3D) matrix platform to generate a tissue-engineered construct in vitro, and then implanted into a patient's body. Successful engineering of heart valves requires a thorough understanding of the different types of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 180 publications
(206 reference statements)
0
54
0
Order By: Relevance
“…Because the majority of this tissue is heterogeneous and contains very fragile cusps, as well as a strong root, the sterilization process can really affect the integrity of cusps easily, that is, the functionality of the valve 24, 25, 26. To verify the superiority of the scCO 2 technique, decellularized porcine aortic valves were sterilized with various sterilization techniques, including the scCO 2 technique.…”
mentioning
confidence: 99%
“…Because the majority of this tissue is heterogeneous and contains very fragile cusps, as well as a strong root, the sterilization process can really affect the integrity of cusps easily, that is, the functionality of the valve 24, 25, 26. To verify the superiority of the scCO 2 technique, decellularized porcine aortic valves were sterilized with various sterilization techniques, including the scCO 2 technique.…”
mentioning
confidence: 99%
“…Precursor cells from blood or heart, infiltrated into the implanted valves. In some observations, the cells in those valves had myofibroblast phenotype confirming their developmental or pathological stage (Jana, Tefft, 2014c, Jana, Tranquillo, 2015. In later case, contraction, thrombosis or mineralization was observed due to presence of non-conducive microenvironment in the valves.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…Conversely, in our study, same VICs showed fibroblast phenotype in a circumferentially oriented nanofibrous membrane (stiffness ~ 230 KPa) which mimics the morphology of the fibrosa layer of an aortic valve leaflet. In a native leaflet, VICs show quiescent fibroblast phenotype; though, their myofibroblast phenotype has been detected in the ventricularis layer of a porcine leaflet, possibly due to shear strain from dynamic motion and thrust during coaptation (Bertipaglia et al , 2003, Jana et al , 2015. The damage to the leaflets in the dynamic environment is restored by their continuous remodeling.…”
Section: Jana and Lerman -31-mentioning
confidence: 95%
See 1 more Smart Citation
“…Other crucial variables to be considered for a fruitful in vitro tissue-engineered valvular production include i) the cell type used for the seeding onto the valvular molds, ii) the culture type, meaning either single cell type cultures or co-culture systems, and iii) ECM production coupled with biomaterial degradation rates [57]. Additionally, cells should be of autologous origin, non-immunogenic, and possessing pronounced plasticity.…”
Section: Regenerative Technologies For Heart Valve Diseasementioning
confidence: 99%